The worldwide COVID-19 pandemic caused a decline in sonographic examinations - is this a continuing trend?: chest = Die weltweite COVID-19-Pandemie führte zu einem Rückgang der sonografischen Untersuchungen – ist dies ein anhaltender Trend? - Kottlors, Jonathan; Fervers, Philipp; Froelich, Matthias F.; Grunz, Jan-Peter; Booz, Christian; Iuga, Andra-Iza; Maintz, David; Heneweer, Carola; Persigehl, Thorsten; Hokamp, Nils Große (RöFo, 2024)
Purpose Due to the increasing number of COVID-19 infections since spring 2020 the patient care workflow underwent changes in Germany. To minimize face-to-face exposure and reduce infection risk, non-time-critical elective medical procedures were postponed. Since ultrasound examinations include non-time-critical elective examinations and often can be substituted by other imaging modalities not requiring direct patient contact, the number of examinations has declined significantly. The aim of this study is to quantify the baseline number of ultrasound examinations in the years before, during, and in the early post-pandemic period of the COVID-19 pandemic (since January 2015 to September 2023), and to measure the number of examinations at different German university hospitals. Materials and Methods The number of examinations was assessed based on a web-based database at all participating clinics at the indicated time points. Results N = 288 562 sonographic examinations from four sites were included in the present investigation. From January 2020 to June 2020, a significantly lower number of examinations of n = 591.21 vs. 698.43 (p = 0.01) per month and included center was performed. Also, excluding the initial pandemic period until June 2020, significantly fewer ultrasound examinations were performed compared to pre-pandemic years 648.1 vs. 698.4 (p < 0.05), per month and included center, while here differences between the individual centers were observed. In the late phase of the pandemic (n = 681.96) and in the post-pandemic phase (as defined by the WHO criteria from May 2023; n = 739.95), the number of sonographic examinations returned to pre-pandemic levels. Conclusion The decline in the number of sonographic examinations caused by the COVID-19 pandemic was initially largely intentional and can be illustrated quantitatively. After an initial abrupt decline in sonographic examinations, the pre-pandemic levels could not be reached for a long time, which could be due to restructuring of patient care and follow-up treatment. In the post-pandemic phase, the pre-pandemic level has been achieved again. The reasons for a prolonged reduction in ultrasound examinations are discussed in this article.
Artikel online veröffentlicht: 13. März 2024
Gesehen am 03.12.2024